PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KONTEKSTUAL UNTUK MATERI BILANGAN BULAT PADA PEMBELAJARAN MATEMATIKA KELAS VII MTsN TANJUNG BONAI AUR SIJUNJUNG - Vera, Yulia Fanrista (Pendidikan Matematika, 2014)
This research was motivated because of the student difficulties in contructing, inquiri, theconcepts, and lack of the learning sources that facilitie the student to learn independentlyis still lacking, and student difficult was to understand the material on a vast integer.Thistype of research is the development of the IDI model. IDI model consists of three stages:define, develop, and evaluate. Student work sheet produced very valid by the validatorcategorized in terms of the feasibility of the content, and language with a final value of3,44. The resulting is also very practical categorized by the students with 85,31% of thefinal value in terms of convenience, time, equivalence, and easily interpreted. This meansstudent work sheet Based on Contexstual Mathematics Learning Material On Class VIIMTsN Tanjung Bonai Aur Suijunjung has valid to be used as teaching materials.